Evaluation of ventilatory threshold and its relation to exercise habits among Japanese - Miyatake, Nobuyuki (Springer Japan, 2010)
OBJECTIVE: The aim of this study was to evaluate aerobic exercise levels, expressed in terms of ventilatory threshold (VT), in a Japanese population and explore the relationship between VT and exercise habits in this population. METHODS: This was a cross-sectional study in which data collected from 547 men and 524 women aged 20–69 years and not on medications, were used to assess exercise habits and parameters at VT, namely, oxygen uptake, work rate, and heart rate. RESULTS: Age-related changes in parameters at VT were noted. Of the participants, 205 men (37.5%) and 142 women (27.1%) had exercise habits. Oxygen uptake and work rate at VT in subjects with exercise habits were significantly higher than those without exercise habits after age had been adjusted for in both sexes. Anthropometric parameters were significantly correlated with oxygen uptake at VT, and the highest correlation coefficient rate was found between oxygen uptake at VT and body fat percentage (men r = −0.589, women r = −0.631). CONCLUSION: The mean values determined here may provide a useful database for evaluating VT in Japanese adult subjects.